Conflicting signals of dry/wet rainfall pattern over the Punjab (Pakistan) during 1961-2015: Complex seasonal changes - Ali, Sajjad; Ajmal, Muhammad; Khattak, Muhammad Shahzad; Shah, Safeer Ullah (Journal of Himalayan Earth Sciences, 2018)
In this study, the spatio-temporal characteristics of seasonal and annual rainfall were analyzed during 1961-2015 over nine selected climatic stations of the Punjab province (Pakistan) to identify the dry/wet rainfall events tendencies (moderate/dry) using the Standardized Precipitation Index (SPI) at 10% significance level. The various values of SPI indicate different levels of dry/wet events. An increasing tendency in moderately dry events was observed at two stations in spring, winter and summer while autumn remained unaffected. Significant increase in percentage of extremely dry rainfall events was seen only at two stations. Moderately wet rainfall events during 1990-2015 (F2) increased significantly at seven stations in winter, one in spring, three stations in summer and autumn compared to the period 1961-1990 (F1). The number of significantly extreme wet rainfall events increased at two, two, three, and seven stations in winter, spring, summer, and autumn respectively. Overall winter is vulnerable to moderately wet rainfall events while summer and autumn are subjected to wet extremes at the majority of stations. Drying tendency has little spatial extent and affected only two stations. Seasonal wetting is mostly concentrated in extreme north, mid- south and middle plains of the Punjab province while most wet events occurred during three decades i.e., 1981-1990, 1991-2000 and 2001-2010, the last being the wettest decade. Extremely wet events together with higher daytime temperature have the potential to disturb normal human life and growth of crops especially in summer. The risk of short-term greatest runoff in summer and autumn is very likely due to rainfall extremes.